The effectiveness of breast lead shielding on scattered radiation in lumbar spine radiography: a phantom study / Khairunnisa Adlina Hairul Anuar - Hairul Anuar, Khairunnisa Adlina; Mahmud, Mohd Hafizi; Leong, Sook Sam; Abd Manan, Khairunnisa (Faculty of Health Sciences, Universiti Teknologi MARA, 2024)
This study evaluates the effectiveness of breast lead shielding in reducing scattered radiation in lumbar spine radiography. Using an anthropomorphic phantom model, an experimental study simulating anteroposterior (AP) and lateral lumbar spine radiography was performed with and without breast shielding. The scattered radiation doses were measured using Radcal ACCU-PRO dosimeter. Significant reductions in scattered radiation dose (42%- 49% reduction) were observed in both AP and lateral projections with the use of breast lead shielding as compared to without shielding (p < 0.001). These findings suggest that breast lead shielding effectively reduces radiation exposure in lumbar spine radiography. The study highlights the importance of using breast shielding to protect patients from scattered radiation. Further research should explore the long-term benefits of shielding, its application in other radiographic procedures and potential advancement in shielding materials and technique.